International trade operations : a guide - Mahayudin, Ismail (Kuala Lumpur : BIMB Institute of Research and Training Sdn Bhd, 1997)
A guidebook on international trade from the Islamic point of view. It touches on the areas of terminology, the banking requirements for proper preparation of shipping documents, international rules on collections and letters of credit, exchange control requirements and the financing of trade.
oif 22/07/16
Loans
Keywords: International trade; Commerce